Imaging features of unusual adrenal masses - Lerttumnongtum P. (2014)
The widespread use of cross-sectional imaging techniques has resulted in increased detection of adrenal masses. The imaging characteristics of common adrenal masses such as adenoma, phaeochromocytoma and metastasis are well established. In this pictorial essay, the imaging features of unusual adrenal masses including cyst, lymphoma, adrenal carcinoma, myelolipoma, haemangioma, smooth muscle tumour, haematoma, and infection (acute tuberculous adrenitis and histoplasmosis) are presented. Computed tomography permits a diagnosis of cyst, acute or subacute haematoma and myelolipoma. Although the imaging features of other lesions are non-specific, imaging has an important role in the detection of these unusual adrenal masses, and in aiding their diagnosis and management.